Women’s Agency and Political Participation in Darjeeling - Binu Sundas (BUANA GENDER : Jurnal Studi Gender dan Anak, 2022)
The demand for the separation of Darjeeling from Bengal goes back to 1907. The demand in the colonial period was not consistent and was limited to the submission of memorandums. During the colonial period, politics was elitist and the common people and women were not part of it. Even after the independence of India, women in Darjeeling did not take part in the movement for the creation of Gorkhaland. Their political participation was limited. It was only in the 1980s when the movement gained momentum that women started to participate. Since then women have been able to use their agency to empower themselves and create their own collective identity and participate in the movement. Post the formation of the Darjeeling Gorkha Hill Council and the emergence of Gorkha Janmukti Morcha women have created a political identity for themselves in the male-dominated political realm. Their shared experiences and beliefs have assisted them in breaking traditional barriers to play a new role of political subjects and transform society by being the agents of change in history.